2018
DOI: 10.1002/ijop.12495
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and pressures of daily life in two West Bank villages—Exploring context and history

Abstract: Interest in the well-being of people exposed to long-term violence and conflict has tended to focus on measurable effects of acute traumatic events, while attention to the pressures of their daily living context is relatively new. Using qualitative and quantitative data from a 2005 survey of all female family caretakers in 2 neighbouring Israeli-occupied West Bank villages (n = 820), we explored the associations of demographic, health-related and contextual factors with reported pressures and WHO-5 well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…This bias corroborates with the excessive focus on trauma that characterizes the discourse of mental health in Palestine and which fails to acknowledge that there are many non-trauma related variables that are associated with increased stress, described as daily contextual stressors (Rabaia et al , 2018). A study on Iraqi people displaced in Jordan showed for instance that unmet needs in relation to income, food or health had a stronger connection to mental distress than trauma exposure (WHO - World Health Organization, 2011 in Rabaia et al , 2018). It is also known that many victims demand social assistance and social justice, rather than mental health services (Summerfield, 1995).…”
Section: De-politicization Of Mental Health By International Organiza...mentioning
confidence: 77%
See 1 more Smart Citation
“…This bias corroborates with the excessive focus on trauma that characterizes the discourse of mental health in Palestine and which fails to acknowledge that there are many non-trauma related variables that are associated with increased stress, described as daily contextual stressors (Rabaia et al , 2018). A study on Iraqi people displaced in Jordan showed for instance that unmet needs in relation to income, food or health had a stronger connection to mental distress than trauma exposure (WHO - World Health Organization, 2011 in Rabaia et al , 2018). It is also known that many victims demand social assistance and social justice, rather than mental health services (Summerfield, 1995).…”
Section: De-politicization Of Mental Health By International Organiza...mentioning
confidence: 77%
“…This approach very easily leads to the labelling of social suffering as a disorder and thus to an over-diagnosis of and a pathologizing of Palestinians as mentally ill. At the same time, the fact that Palestinians are suffering from political determinants of health becomes obscured and normal reactions to social injustice are being conflated as disorders (Rabaia et al, 2010). This bias corroborates with the excessive focus on trauma that characterizes the discourse of mental health in Palestine and which fails to acknowledge that there are many non-trauma related variables that are associated with increased stress, described as daily contextual stressors (Rabaia et al, 2018). A study on Iraqi people displaced in Jordan showed for instance that unmet needs in relation to income, food or health had a stronger connection to mental distress than trauma exposure (WHO -World Health Organization, 2011 in Rabaia et al, 2018).…”
Section: De-politicization Of Mental Health By International Organiza...mentioning
confidence: 96%
“…The WHO-5 asks participants to rate their subjective psychological well-being (e.g., positive mood, vitality) on a six-point scale (0 = at no time to 5 = all of the time) over the past two weeks (e.g., "I have felt cheerful and in good spirits"). The scale has been used in a study that examined the well-being of female family caretakers in two neighboring Israeli-occupied West Bank villages [34]. A total score was computed by summing all items (Cronbach's α = 0.84).…”
Section: Methodsmentioning
confidence: 99%
“…This said, much remains to be learnt about psychological well-being and life satisfaction in child victims of war or about the coping abilities and survival skills that they can potentially display in severely compromised living environments (Linton, Kennedy, Shapiro, & Griffin, 2018; Rabaia, de Jong, Abdullah, Giacaman, & van de Ven, 2018). Although the scientific literature extensively describes the child victims of conflict and violence as highly vulnerable, a growing corpus of studies points up sources of resilience that can be available to these children (Barber, 2013; Halevi, Djalovski, Vengrober, & Feldman, 2016; Veronese & Castiglioni, 2015).…”
Section: Introductionmentioning
confidence: 99%